Early Retirement Provisions and the Labor Force Behavior of Older Men: Evidence from Canada - Baker, Michael; Benjamin, Dwayne (Journal of Labor Economics, 1999)
We examine the (sequential) introduction of early retirement provisions to Canada's two public pension plans. These reforms provide a unique opportunity to assess the effect of public pension plan parameters on labor supply behavior, free of the biases that potentially affect the simple time‐series or cross‐section inference presented in many previous studies. We find that the reforms led to an increase in pension receipt but had little immediate effect on labor market behavior. This is due to the fact that men who initially took advantage of the early retirement provisions would otherwise have had limited labor market participation.